ANALISA KEMAMPUAN SISWI SMK DALAM PENGKLASIFIKASIAN GEJALA ABIOTIK (SIFAT FISIKA) DAN GEJALA BIOTIK SERTA KAITANNYA DENGAN BIDANG KEMARITIMAN - Lusiani; Andi Hendrawan; Sumarno Wally (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2020)
The objectives to be achieved in this study are to analyze the ability of vocational high school students to classify abiotic symptoms (physical properties) and biotic symptoms and their relation to the maritime field. The method in this research is a combination of survey and literature study. In this study the authors took location at SMK Bina Bhakti Cilacap. The instrument used was using worksheets / student activities / abiotic symptoms and applied physics biotics. The analysis used is Descriptive Statistics Frequencies. Comparison of standard deviations. The comparison results show that the standard empirical deviation (s = 7,649) is higher than the hypothetical standard deviation (σ = 5). This shows that the ability of students in classifying abiotic symptoms (physical properties) and biotic symptoms related to maritime fields has high variation. In other words, the ability of subjects to one another is not uniform or have differences. Based on the analysis and discussion that has been done, it can be concluded that the ability of students in classifying abiotic symptoms (physical properties) and biotic symptoms related to the maritime field has high variations. This means that vocational students generally have different abilities in classifying abiotic symptoms (physical properties) and biotic symptoms related to the maritime field.